The transcriptional regulatory network mediated by banana (Musa acuminata) dehydration‐responsive element binding (MaDREB) transcription factors in fruit ripening. Issue 2 (3rd January 2017) - Kuang, Jian‐Fei; Chen, Jian‐Ye; Liu, Xun‐Cheng; Han, Yan‐Chao; Xiao, Yun‐Yi; Shan, Wei; Tang, Yang; Wu, Ke‐Qiang; He, Jun‐Xian; Lu, Wang‐Jin
Summary: Fruit ripening is a complex, genetically programmed process involving the action of critical transcription factors (TFs). Despite the established significance of dehydration‐responsive element binding (DREB) TFs in plant abiotic stress responses, the involvement of DREBs in fruit ripening is yet to be determined. Here, we identified four genes encoding ripening‐regulated DREB TFs in banana ( Musa acuminata ), MaDREB1, MaDREB2, MaDREB3, and MaDREB4, and demonstrated that they play regulatory roles in fruit ripening. We showed that MaDREB1–MaDREB4 are nucleus‐localized, induced by ethylene and encompass transcriptional activation activities. We performed a genome‐wide chromatin immunoprecipitation and high‐throughput sequencing (ChIP‐Seq) experiment for MaDREB2 and identified 697 genomic regions as potential targets of MaDREB2. MaDREB2 binds to hundreds of loci with diverse functions and its binding sites are distributed in the promoter regions proximal to the transcriptional start site (TSS). Most of the MaDREB2‐binding targets contain the conserved (A/G)CC(G/C)AC motif and MaDREB2 appears to directly regulate the expression of a number of genes involved in fruit ripening. In combination with transcriptome profiling (RNA sequencing) data, our results indicate that MaDREB2 may serve as both transcriptional activator and repressor during banana fruit ripening. In conclusion, our study suggests a hierarchical regulatory model of fruit ripening in banana and that the MaDREB TFs may act as transcriptional regulators in the regulatory network.